Perancangan Ontologi Semantik: Representasi Digital Film Bioskop Indonesia - Fadillah, Andien Rachma; Noviyanti, Komang Kartika; Wiguna, I Putu Agus Arya; Pramartha, Cokorda (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 12 No 4 (2024): JELIKU Volume 12 No 4, May 2024, 2024)
The rapid growth of the film industry in Indonesia has created complexity in the management and integration of cinema-related data. Despite the increase in film production, audience enthusiasm remains unmet due to inadequate film infrastructure and difficulties in accessing information. Semantic Web technology can be a solution by expanding the current web to provide better-defined meanings to information, enabling collaboration between humans and computers. This research aims to develop an ontology for Indonesian cinema to enhance the representation and interoperability of information. Ontology, as a model of structured knowledge representation using the Web Ontology Language (OWL), allows machines to better understand information. The ontology focuses on crucial aspects such as film titles, genres, film crew information, release years, age ratings, and more. It is expected that this ontology provides a solid foundation for more efficient data search, analysis, and processing applications to support the Indonesian entertainment industry. Initial testing involves user questions, and it is anticipated that this ontology model can systematically present national cinema information.